Efforts To Prevent Money Politic, Bribery Crimes To Realize Dignified Simultaneous Elections In 2024 In Indonesia - Rizky Pratama Putra Karo Karo (Universitas Widya Gama Malang, 2023)
The largest democratic party in Indonesia will win simultaneous elections in 2024. The Indonesian people have a right to elect a leader who is willing to serve them and does not engage in corruption. To produce a dignified general election, this simultaneous election must be performed in accordance with the law. The goal of this study is to examine and outline initiatives in Indonesia to avoid voter bribery and ensure fair elections. The normative research method was employed. To reach deductive conclusions, researchers use qualitative study of legal materials. Bribery is a criminal crime, according to the study's findings. Bribery, in addition to other criminal behaviors, might jeopardize the goal of peaceful elections. A dignified general election is one in which citizens can live in peace before, during, and after voting. Various parties use mass socialization through various media to carry out prevention activities. The socialization that can be done is about the criminal threat of bribery; second, about the people's involvement in creating dignified elections by refusing to accept bribes and choosing the best leadership candidates.